Excitation–emission matrices applied to the study of urban effluent discharges in the Chubut River (Patagonia, Argentina) - Chiarandini Fiore, Jessica Paola (2013)
Natural and contaminated waters of the final reaches of the Chubut River (Patagonia, Argentina) were studied to obtain information about river organic matter and effects of domestic and industrial discharges (fishery effluents and sewages). Fluorescence Excitation-Emission Matrices (EEMs) were obtained from samples only filtered (0.45 μm) and diluted, if necessary, to avoid the inner filter effect. In addition, physicochemical parameters were measured to know the quality of the water and the effluents. Results show that EEMs allow a rapid and simple control of the effluents from fisheries and domestic sewage in Chubut River estuary, necessary to take management decisions.